Dual Modulation of Single Molecule Conductance via Tuning Side Chains and Electric Field with Conjugated Molecules Entailing Intramolecular OS Interactions. Issue 17 (17th April 2022) - Zhang, Hua; Xu, Wei; Song, Kai; Lu, Taige; Zhang, Guanxin; Zang, Yaping; Hong, Wenjing; Zhang, Deqing
Abstract: Herein, single‐molecule conductance studies of TBT1‐TBT6 which entails 1, 4‐dithienylbenzene as the backbone and SMe groups as the anchoring units, with the scanning tunneling microscope break junction (STM‐BJ) technique, are reported. The molecular conductance of TBT1 with intramolecular OS noncovalent interactions is enhanced by about one order of magnitude in comparison to their analogue TBT2 (which contains alkyl instead of alkoxy chains). By replacing the methoxy groups in TBT1 with extending alkoxy chains in TBT3, TBT4, and TBT5, the molecular backbones become twisted and as a consequence the single‐molecule conductance decreases gradually, showing that the intramolecular OS noncovalent interaction is influenced by the structural features of alkoxy chains. More importantly, the single‐molecule conductance of TBT3, TBT4, and TBT5 can be boosted by increasing the electric field applied to the molecular junctions. Remarkably, the conductance of TBT3, TBT4, and TBT5 can be reversibly modulated due to the conformational changes between twisted and planar ones by varying the electric field. These results demonstrate that molecules with intramolecular OS noncovalent interactions have the potential for in situ control of the electrical properties of molecular‐scale devices. Abstract : Here, single‐molecule conductance studies for molecules with 1, 4‐dithienylbenzene as the backbone and SMe groups as the anchoring units by using the STM‐BJ technique are reported. The results show that the single‐molecule conductance can be tuned by varying side chains and electric field through influencing the intramolecular OS interactions and molecular conformation within the metal–molecule–metal junctions.